Self-prioritization in vision, audition, and touch. - Schäfer, S; Wesslein, A; Spence, C; Wentura, D; Frings, C (Springer Berlin Heidelberg, 2016)
To investigate self-prioritization independently of stimulus familiarity, Sui et al. (J Exp Psychol Hum Percept Perform 38:1105-1117, 2012. doi: 10.1037/a0029792 ) introduced a new paradigm in which different geometric shapes are arbitrarily associated with self-relevant (e.g., "I") and neutral labels (e.g., "stranger"). It has now been repeatedly demonstrated that in a subsequently presented matching task, this association leads to faster and more accurate verifications of self-relevant shape-label pairings than neutral shape-label pairings. In order to assess whether this self-prioritization effect represents a general selection mechanism in human information processing, we examined whether it is limited to the visual modality. Therefore, besides visual stimuli, auditory and vibrotactile stimuli were also associated either to self-relevant or to neutral labels. The findings demonstrate that self-prioritization represents a general tendency influencing human information processing, one that operates across the senses. Our results also highlight a top-down component to self-prioritization.